La naturaleza del hábito de la virtud: el problema del vicio considerado como hábito según Tomás de Aquino. - Buzeta Undurraga, Sebastián (Scripta Mediaevalia, 2026)
The theory of virtue, and with it the essence of habit, according to Thomas Aquinas has been extensively developed by his commentators up to the present day. A central aspect of the essence of habit, and specifically of operative habits, is that it looks directly to nature (as something connatural) having potency as its subject. This leads to the question of whether vice is formally a habit or not, because, on the one hand, Aquinas is explicit in affirming that vice is a habit, but, on the other hand, he also affirms that instead of perfecting man it imperfects him, since it orients him in a sense contrary to nature. Thus, in this paper we propose, first, to identify whether vice is formally a habit in the thought of St. Thomas and, second, the way in which vice should be understood from the very conception of St. Thomas based on an analysis of the essence of habit.